2009
DOI: 10.1016/j.febslet.2009.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Acute activation of acid ceramidase affects cytokine‐induced cytotoxicity in rat islet β‐cells

Abstract: a b s t r a c tCeramidase hydrolyzes ceramide and produces sphingosine as a substrate of sphingosine kinase (SPHK), which transforms sphingosine to sphingosine-1-phosphate. It has been reported that cytokines elicit SPHK activation in rat b-cells. As a sphingosine provider, ceramidase should also be activated. In our previous work, we showed that the increase in mRNA and protein levels in cytokinetreated INS-1 rat b-cells resulted in chronic activation of neutral ceramidase. Here we found that acid ceramidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
(55 reference statements)
3
12
0
Order By: Relevance
“…Moreover, increases in ceramide mass under these conditions were only observed in RINm5F cells, 19 but not β-TC3 cells 17 . These modest or non-significant effects are perhaps consistent with observations that cytokines can activate both neutral and acidic ceramidases in β-cells, 21 , 22 which would tend to counteract any ceramide accumulation. Pharmacological inhibitors of ceramide synthesis or SMase activity also failed to alter IL-1β-stimulated responses in a rat β-cell line, 23 although the potentiation of IL-1β effects on cell death by TNFα might involve an enhanced sensitivity to basal acid SMase 24 .…”
Section: Sphingolipids and Type 1 Diabetessupporting
confidence: 83%
“…Moreover, increases in ceramide mass under these conditions were only observed in RINm5F cells, 19 but not β-TC3 cells 17 . These modest or non-significant effects are perhaps consistent with observations that cytokines can activate both neutral and acidic ceramidases in β-cells, 21 , 22 which would tend to counteract any ceramide accumulation. Pharmacological inhibitors of ceramide synthesis or SMase activity also failed to alter IL-1β-stimulated responses in a rat β-cell line, 23 although the potentiation of IL-1β effects on cell death by TNFα might involve an enhanced sensitivity to basal acid SMase 24 .…”
Section: Sphingolipids and Type 1 Diabetessupporting
confidence: 83%
“…Take together, our data suggest that NCDase inhibition is involved in Palm-induced apoptosis in INS-1 cells via blocking ceramide degradation and NCDase inhibition may be a novel pathway for ceramide accumulation, in addition to the ceramide synthesis de novo. Previously, we had reported that INS-1 cells exhibited basal NCDase activity [16], basal acid CDase activity was also detected in INS-1 cells and isolated rat islets [27]. In current study, we found that Palm treatment reduced mRNA and protein levels of NCDase, suppressing its activity and accumulating ceramide.…”
Section: Discussionsupporting
confidence: 53%
“…Increased sphingolipid metabolites that are observed during lipotoxicity also induce β-cell dysfunction, leading to apoptosis (49). For example, increased intracellular ceramide promotes an apoptotic cascade and initiates β-cell death in diabetic fatty rodent models of T2D in vivo and human β-cells in vitro (5052). …”
Section: The Role Of Sphk/s1p Signalling In the Development Of Diamentioning
confidence: 99%